Guided Inquiry Assisted by Scaffolding in Biology Learning: A Solution to Improve Students Critical Thinking and Metacognitive Supporting SDG 4 (Quality Education) - Alfito Deanoval; Yuni Gayatri; Lina Listiana (Postgraduate, University of Mataram, 2026)
This study purposed to determine the effect of guided inquiry learning assisted with scaffolding on students’ critical thinking and metacognitive skills. This quasi-experimental study employed a pretest-posttest control group design. The study was conducted at SMA Negeri 1 Gondang Mojokerto with the research subject being 11th-grade science students, involving a control group using conventional instruction and an experimental group using guided inquiry learning supported by scaffolding. Data were collected through tests, using research instruments in the form of critical thinking and metacognitive essay test. Data were analayzed using the Mann-Whitney test and the N-Gain test. After being implemented with the guided inquiry learning model supported with scaffolding, critical thinking skills increased to 67.45 in the medium category. The results of the Mann-Whitney test showed a significant difference (p = 0.05). furthermore, in the N-Gain test analysis, the experimental group scored 57.59 in the moderately effective category, while the control group scored 7.39 in the ineffective category. The analysis of metacognitive skills revealed that the experimental group’s metacognitive skills were at 56.30 in the moderately effective category. It means that guided inquiry supported with scaffolding is affective in improving critical thinking and metacognitive skills.